Efeito da frequência de inundação na estrutura do manguezal da Baía de Vitória, Espírito Santo, Brasil - Lima, Tatiane Matuchack Joseph (2011)
Inundation frequency and water table depth determine mangrove forests environmental and stressors gradients, consequently, mangrove ecosystem function and structure. This study analyses inundationfrequency, water table depth and salinity influencesin mangrove forests species composition and development in Baía de Vitória, Espírito Santo State, Brazil. Transects were establishedconsidering structural heterogeneity. Plot method was applied to structure characterization. Microtopographicprofileswere obtained and estimated inundation frequency. Monthly, interstitial water salinity and water table depthwere measured. Rhizophora mangleoccurredin moreinundated and less saline areas. Avicennia schauerianaoccurredin less inundated and more saline areas asLagunculariaracemosa. The latter dominated in deep water table areas. Inundation frequencies equal or superior to 80% resulted in high structural developmentforests. 46% inundation frequency can be considered limiting, when there isn’t a freshwater source. Species distribution reflected mostly external factors, considering that studied abiotic variables explained 58,4%of structural variation. Zonation monitoring would indicate hydrological alterations resulting from anthropic activities and climate change.